A study of pre-operative predictors for conversion to open surgery in emergency laparoscopic appendectomy - Kodliwadmath, Harsha B.; Srinivas Pai, B.; Sphurti Kamath, K. (International Surgery Journal, 2020)
Background: Acute appendicitis is one of the most common emergencies encountered by surgeons. Although laparoscopic appendectomy is the preferred approach complicated appendicitis with a mass, abscess or perforation do present with a challenge to the operating surgeon compelling him to convert to open surgery. Our study aimed at identifying pre-operative factors that would help us predict the risk of conversion to open surgery. Methods: This was a prospective analytical study. All cases admitted over a period of one year undergoing emergency appendectomy were included in the study. The duration of history, clinical presentation, laboratory and radiological investigations were noted. The reason for conversion to open surgery was recorded. The post-operative stay and complications were analyzed. Results: A total of 160 patients fulfilling the inclusion criteria were included in the study. The mean age was 33.78 years with a male preponderance of 58%. The duration of history, clinical and radiological evidence of complicated appendicitis and peritonitis, total leucocyte count and serum bilirubin levels were identified as pre-operative predictors for risk of conversion to open surgery from laparoscopic appendectomy. Conclusions: These predictors are useful in predicting conversion to open surgery in laparoscopic emergency appendectomy. In these cases, proceeding with an open surgical approach may be beneficial to the patient in reducing operative time, cost, hospital stay and complications as laparoscopic approach may prove to be unsuccessful. This would help in enhanced communication between the surgeon and the patient with respect to the outcome and prognosis.